Peculiarities of morphogenesis of universal hematopoesis and immune protection in fetuses of domestic pig - Gavrilin, P.; Gavrilin, P. N.; Gavrylin, P.; Gavrylin, P. M.; Havrylin, P. M.; Havrylin, P.; Gavrilin, Pavlo; Gavrilin, Pavel; Гаврилін, Павло Миколайович; Oliyar, A. V.; Oliiar, A.; Оліяр, Алла Вячеславівна; et al. (Інститут біології тварин НААН України, 2016)
It was established that prenatal skeletal ontogeny in domestic pigs is presented in two forms: structural and functional bone marrow osteoblast (bone formation) and hematopoietic (blood-forming) development and structural and functional transformation that is taking place in parallel, different speeds towards vectors which are in particular histogram and cytoarchitectonic in different zonal centers of ossification of the skeleton in the fetus. The main structural components of the bone marrow domestic pig fetal within cells of the bone marrow centers of ossification of the bone shaft located in some models directly related to the dynamics of quantitative tissue components. In the fetuses of especially late in the fetal period of ontogenesis (from 3 months) against the background of almost complete disappearance of hematopoietic centers in the liver begin to form as an unfinished structure segments with indistinct borders and lobules, although expressive (Relief) with outline radial hepatocyte structure and separated from each other with a thick connective tissue. The basic characteristics, structural and functional bone marrow of the domestic pig fetuses are: localization in the spongy bone, leading to skeletal ossification centers, clearly marked morphological heterogeneity of the osteogenic distribution peripheral and central – hematopoietic form. Zonal structure of hematopoietic marrow gives the presence of islets and islet diffuse, with topographically distinct sections. Встановлено, що в пренатальному періоді онтогенезу у скелеті свині свійської присутні дві структурно-функціональні форми кісткового мозку: остеобластична (кісткоутворювальна) та гемопоетична (кровотворна), розвиток і структурно-функціональна трансформація яких проходить пара¬лельно, з різною швидкістю та векторами напрямку, що в сукупності проявляється особливостями його зональної гісто- та цитоархітектоніки в різних осередках окостеніння скелета плодів. Основні структурні компоненти кісткового мозку у плодів свині свійської в межах кістковомозкових вічок осередків окостеніння кісткових органів розташовуються у певній закономірності та безпосередньо взаємопов’язані з кількісною динамікою тканинних компонентів. У плодів свині свійської, особливо наприкінці плідного періоду онтогенезу (починаючи з 3-місячного віку), на тлі майже повного зникнення центрів гемопоезу, в печінці починають формуватися як часточки незавершеної структури з нечіткими межами, так і часточки, що мають виразні (рельєфні) контури радіальних балок гепатоцитів і відокремлені одна від одної потовщеною сполучною тканиною. Основними структурно-функціональними характеристиками кісткового мозку плодів свині свійської є: локалізація в губчастій кістковій речовині основних осередків окостеніння скелета, чітко виражена морфологічна гетерогенність з розподілом на периферичну остеогенну та центральну – гемопоетичну форми, зональна структура кровотворного кісткового мозку з наявністю острівцевих та дифузно- острівцевих, топографічно відокремлених ділянок.
Особливості морфогенезу органів універсального кровотворення та імунного захисту у плодів свині свійської
Keywords: ossification centers; осередки окостеніння; liver; печінка; bone marrow; кістковий мозок; fetal domestic pig; плоди свині свійської